Pengaruh Model Pembelajaran Pair Cheks Berbasis Tugas Pengajuan Masalah terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Muksin Muksin; Tataq Yuli Eko Siswono; Rooselyna Ekawati (Universitas Syiah Kuala, 2020)
The students' problem solving ability is low. One effort that can be done is to implement the pair checks type of cooperative learning. This study aims to determine the effect of the pair checks type of cooperative learning based on the task of problem posing on students' mathematical problem solving abilities. This research is a quasi experimental research. The population of this study were students of grade 8. The sample consisted of two classes selected by random sampling. The instruments used in this study were test and questionnaire. The data were obtained from the results of the post test after implement the pair check type of cooperative learning. Data were analyzed using t-test. The results showed that there was a significant effect of the pair checks type of cooperative learning based on the task of problem posing on students' mathematical problem solving abilitie. In addition, there was a difference in the increase indicated by the N-gain value in the experimental clas. Therefore, the pair checks type of cooperative learning based on the task of problem posingan effect on improving students' problem-solving abilities.